Effective approaches towards microstructural strain mapping of AZ31B Mg sheet material using digital image correlation. (March 2018) - Nagarajan, Srinivasan; Jain, Mukesh K.; Wilkinson, David S.; Mishra, Raja K.
Highlights: A simple, fast and cost-effective specimen surface patterning procedure based on chemical etching has been proposed to study the microstructural strain evolution in AZ31B Mg alloy using digital image correlation. The accuracy and precision of conventional and incremental digital image correlation methods to calculate microstructural strain for various subset sizes and strain levels have been experimentally investigated. For smaller subset size, incremental method yields better accuracy and precision than the conventional method. Decorrelation is also found to be minimal in incremental method. Abstract: A simple, fast, cost-effective and robust specimen surface patterning procedure based on chemical etching has been developed to obtain microstructural strain fields using digital image correlation (DIC) in AZ31B Mg alloy. Due to extensive changes in the microstructural features and surface roughening during deformation of Mg alloys, conventional DIC strain calculation can lead to erroneous results as well as loss of correlation (decorrelation) in local zones in the microstructural field. Therefore, an incremental DIC scheme has been explored in this study to map the full field microstructural strain distribution in AZ31B Mg sheet subjected to large tensile strains. It is shown that compared to conventional correlation, the incremental scheme maps microstructural strain fields with minimal decorrelation in localized zones up to large macroscopic plastic strains. The error and standard deviation in the microstructural strain calculated using conventional correlation follows a decreasing trend with increase in subset size, whereas those calculated by the incremental scheme are almost constant with subset size variation. The results suggest that for microstructural strain calculation requiring high spatial resolution (i.e. smaller subset size), incremental correlation yields better accuracy and precision than the conventional scheme irrespective of the magnitude of strain.